An integrated multi‐layered analysis of the metabolic networks of different tissues uncovers key genetic components of primary metabolism in maize. (24th February 2018) - Wen, Weiwei; Jin, Min; Li, Kun; Liu, Haijun; Xiao, Yingjie; Zhao, Mingchao; Alseekh, Saleh; Li, Wenqiang; de Abreu e Lima, Francisco; Brotman, Yariv; Willmitzer, Lothar; Fernie, Alisdair R.; et al.
SUMMARY: Primary metabolism plays a pivotal role in normal plant growth, development and reproduction. As maize is a major crop worldwide, the primary metabolites produced by maize plants are of immense importance from both calorific and nutritional perspectives. Here a genome‐wide association study (GWAS) of 61 primary metabolites using a maize association panel containing 513 inbred lines identified 153 significant loci associated with the level of these metabolites in four independent tissues. The genome‐wide expression level of 760 genes was also linked with metabolite levels within the same tissue. On average, the genetic variants at each locus or transcriptional variance of each gene identified here were estimated to have a minor effect (4.4–7.8%) on primary metabolic variation. Thirty‐six loci or genes were prioritized as being worthy of future investigation, either with regard to functional characterization or for their utility for genetic improvement. This target list includes the well‐known opaque 2 ( O2 ) and lkr / sdh genes as well as many less well‐characterized genes. During our investigation of these 36 loci, we analyzed the genetic components and variations underlying the trehalose, aspartate and aromatic amino acid pathways, thereby functionally characterizing four genes involved in primary metabolism in maize. Significance Statement: This study presents the most comprehensive data sets for maize primary metabolism with 61 known primary metabolites measured across multiple tissues using a large association panel. The combination of genome‐wide association study with metabolomic, transcriptomic and transgenic approaches enables dissection of key genetic components of maize primary metabolism, thereby facilitating maize improvement.